Modis : A Market-Oriented Deposit Insurance Scheme - Zoli, Edda.; Vaez-Zadeh, Reza.; Xie, Danyang (Washington, D.C. : International Monetary Fund, 2002)
This paper argues that an optimal deposit insurance scheme would allow the level of insurance coverage to be determined by the market. Based on this principle, the paper proposes an insurance scheme that minimizes distortions and embodies fairness and credibility, two essential characteristics of a viable and effective deposit insurance scheme. Using a simple model for the determination of the optimal level of insurance coverage, it is shown that the optimal coverage is higher for developing compared to developed countries; a condition that is broadly satisfied by prevailing deposit insurance practices around the world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet